Polymer nanofibers : building blocks for nanotechnology - Pisignano, Dario (Cambridge : Royal Society of Chemistry, 2013)
Research into polymer nanofibers has increased significantly over the last decade, prompting the need for a comprehensive monograph examining the subject as knowledge of their properties and potential applications has increased.Postgraduate students and researchers new to the field will benefit from the'from materials to applications' approach to the book, which examines the physio-chemical properties in detail, demonstrating how they can be exploited for a diverse range of applications, including the production of light and wound dressings. Techniques for the fabrication, notably electrospinning, are discussed at length.This book provides a unique and accessible source of information, summarising the last decade of the field and presenting an entry point for those entering the field and an inspiration to established workers. The author is currently the national coordinator for several research projects examining the applications of polymer nanofibers, alongside active international collaborations.
Keywords: Nanofibers